Analysis of Medications Returned During a Medication Take-Back Event - Christina H.J. Yang; Mitesh Doshi; Nancy A. Mason (MDPI AG, 2015)
A medication take-back event was held in Lansing, MI, USA, for four hours in September 2013. The objective was to quantify medication waste by determining the ratio of medication units remaining versus dispensed and to identify therapeutic classes with greater ratios of remaining medication units. Drug name, strength, quantity remaining, quantity dispensed, dispensary source, and brand or generic were recorded from the label of each medication container returned. Out of the over 3600 medication containers collected, this study analyzed 2459 containers, which included 304 controlled substances. On average, 66 percent of the medications dispensed in these containers were unused, and therefore wasted. Immunologic medications had the lowest quantity of waste at 54%, while geriatrics/miscellaneous therapeutic class yielded the highest quantity of waste at 79%. The most common therapeutic classes collected were pain/spasm, cardiovascular, and mental health. Greater emphasis on patient education regarding medication adherence and health care professionals' judicious prescribing habits is warranted to reduce the frequency of unused medications. The increased accessibility to medication return sites may alleviate the prevalence of medication accumulation, environmental damage, and medication misuse.